2014
DOI: 10.1007/s00330-014-3276-9
|View full text |Cite
|
Sign up to set email alerts
|

MR-sequences for prostate cancer diagnostics: validation based on the PI-RADS scoring system and targeted MR-guided in-bore biopsy

Abstract: • T2WI + DWI + DCE achieved the highest accuracy in patients with higher grade PCa • T2WI + DWI + DCE was more accurate for peripheral- than for transitional-zone PCa • DCE increased PCa detection accuracy in the peripheral zone • DWI was the leading sequence in the transitional zone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(56 citation statements)
references
References 22 publications
4
49
1
1
Order By: Relevance
“…A second group using four-parameter MP-MRI of the prostate did not calculate a sum score, but described a limited clinical utility for 1 H-MRSI. Using three parameters, investigators have reported a sensitivity of 80-95 %, a specificity of 62-92 %, and an area under the ROC curve of 69-97 % [9,10,12,[17][18][19]. These findings are in good agreement with our results, showing similar sensitivity and specificity.…”
Section: Discussionsupporting
confidence: 95%
See 2 more Smart Citations
“…A second group using four-parameter MP-MRI of the prostate did not calculate a sum score, but described a limited clinical utility for 1 H-MRSI. Using three parameters, investigators have reported a sensitivity of 80-95 %, a specificity of 62-92 %, and an area under the ROC curve of 69-97 % [9,10,12,[17][18][19]. These findings are in good agreement with our results, showing similar sensitivity and specificity.…”
Section: Discussionsupporting
confidence: 95%
“…We chose this approach, as the latest PI-RADS version (v2) does not include 1 H-MRSI in its specific reporting recommendations. On the other hand, the used sum score has shown to be valid, robust, and reliable approach by several researchers [8][9][10][11][12][13].…”
Section: Diagnostic Criteria In Mp-mrimentioning
confidence: 98%
See 1 more Smart Citation
“…MpMRI included T2-and T1-weighted images, diffusion-weighted imaging (DWI), and perfusion imaging (DCE-MRI). The imaging protocol was adapted to the ESUR (European Society of Urogenital Radiology) and has been previously published (Schimmöller et al 2014). DCE-MRI images were post-processed using the DynaCAD software (Invivo, Orlando, FL, USA).…”
Section: Mr Imagingmentioning
confidence: 99%
“…Diffusion-weighted imaging (DWI) is one of the essential techniques in mp-MRI [3,4]. Further, DWI enables measurement of the apparent diffusion coefficient (ADC), which can be used to predict Gleason score [5,6].…”
Section: Introductionmentioning
confidence: 99%